If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+4)=-3x+8+5x
We move all terms to the left:
2(x+4)-(-3x+8+5x)=0
We add all the numbers together, and all the variables
2(x+4)-(2x+8)=0
We multiply parentheses
2x-(2x+8)+8=0
We get rid of parentheses
2x-2x-8+8=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 8+7b=9b | | (16x-50)=(9x+34) | | 6x+4=-4x+114 | | -3+21x=39x+3=180 | | 1.5(p+5)=12 | | 3x-2x=100-5x | | 3y-10=3y-10 | | -6+5u=2u | | 6z+17+73=180 | | 2x+23+14=-23-4x | | 3y-11y+6-7y=54 | | -4x-1=7x+43 | | 4x-15=5x+6 | | 6.4+3x=23.5 | | 2x+4=x-29 | | 15+2x-5=-7x-5-6x | | y+10=44 | | 5+4y=-7+4y | | (7x-5)+X=46 | | x-10=46 | | 5x+17+73=180 | | 5(x+2)-3x=24 | | –4j+4=–3j | | 7(1x-2)=8(x-8) | | 5p+1.5=12 | | y/4+-3=0 | | 3/5s-5/4=s/8+5/4 | | 3x+2x=100-5x | | 30/120=1.5/x | | 3b+3+1=4 | | 0.7h-8=0.2h-6 | | 13=3(w+6)-8w |